2020
DOI: 10.1177/1099800420908002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Old Photos in Reminiscence Therapy in Elderly Women With Depressive Symptoms: A Functional Magnetic Resonance Imaging Study

Abstract: Background: Although evidence shows that reminiscence therapy relieves depression in the elderly, few studies have explored its mechanisms and it is unclear whether old public photos rather than personal photos are effective prompts. Objectives: The aims of this functional magnetic resonance imaging (fMRI) study with an event-related design were to explore whether old public photos can evoke autobiographical memories and compare brain-activation responses to photos between elderly women with depressive symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Notably, left STG showed a higher activation when participants classified past events compared to future events, suggesting that this area is involved in accessing past information. In agreement with this view, several studies showed that the left STG (and particularly Broadman Area 22) is recruited to successfully recall names (Yagishita et al, 2008) or images (Wu et al, 2020), disclosing its role in memory-related processing. On the other hand, when participants classified future compared to past events, the left superior frontal gyrus (SFG) activation increased.…”
Section: Discussionmentioning
confidence: 63%
“…Notably, left STG showed a higher activation when participants classified past events compared to future events, suggesting that this area is involved in accessing past information. In agreement with this view, several studies showed that the left STG (and particularly Broadman Area 22) is recruited to successfully recall names (Yagishita et al, 2008) or images (Wu et al, 2020), disclosing its role in memory-related processing. On the other hand, when participants classified future compared to past events, the left superior frontal gyrus (SFG) activation increased.…”
Section: Discussionmentioning
confidence: 63%
“…Based on these criteria, we analysed 305 studies, from which we excluded 281 studies, and included 5 other studies from the bibliographic search, finally including 19 studies (14 from database and registers and 5 from other methods) published before 2023 [ 17 , 19 , 20 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. We report the search flow diagram in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…For older people, old public photographs can stimulate autobiographical memories to achieve the effect of reminiscence therapy (Wu et al, 2020). Therefore, four themes of old photographs were collected: Showa era, landscape, food and festival.…”
Section: Materials and Participantsmentioning
confidence: 99%